The Effect of Goat Testicular Extract on The Sex Ratio of Guppy Fish (Poecilia reticulata) - Aripin, Agin; Mustahal, Mustahal; Syamsunarno, Mas Bayu (Agrikan Jurnal Agribisnis Perikanan, 2021)
The guppy fish is a type of ornamental fish commodity that is widely cultivated, especially male guppies with advantages such as varied colors, shapes and patterns so that they are more in demand. The purpose of this study was to determine the optimal dose of goat testicle extract against the masculinization process of guppies (Poecilia reticulata). The design method used was a Completely Randomized Design with four treatments and replicated doses were 0 ml/l, 3 ml/l. 6ml/l and 9 ml/l goat testicular extract with 24-hour immersion. The broodstock of guppies was then maintained in different containers for two days, and the spawning process was carried out en masse with a ratio between males and females 1:2 for four days and given natural food 2x a day. The fry fed was born and then reared for 63 days with artificial feed, namely Artemia sp. and silkworms. The results obtained that the administration of goat testicular extract had affected the masculinization of guppies. Administration with a dose of 9 ml/l resulted in the highest male sex ratio of 69.13Â±5.92% and survival rate of 90.16Â±10.00%.